Ephemeroptera, Plecoptera and Trichoptera assemblages in two Atlantic Rainforest streams, Southeastern Brazil - Crisci-Bispo, Vera L. [UNESP]; Bispo, Pitágoras C. [UNESP]; Froehlich, Claudio G. (Sociedade Brasileira de Zoologia, 2007)
Comunidades de Ephemeroptera, Plecoptera e Trichoptera (EPT) em substrato rochoso foram estudadas em dois riachos do Parque Estadual Intervales. Coletas com um amostrador de Surber (10 subamostras aleatórias, 1 m²) foram feitas mensalmente de setembro de 1999 a setembro de 2000 e trimestralmente de dezembro de 2000 a setembro de 2001 nos Ribeirões Bocaina e Água Comprida. A fauna de EPT do Ribeirão Bocaina foi mais diversificada e mais abundante do que a do Ribeirão Água Comprida. A fauna de EPT foi bastante diferente entre os dois riachos, tanto do ponto de vista da composição faunística quanto do ponto de vista funcional. Os resultados indicaram que não houve um padrão sazonal claro da variação temporal da densidade.

Assemblages of Ephemeroptera, Plecoptera and Trichoptera (EPT) of rocky substrates were studied in two streams of the Intervales State Park. Monthly collections with a Surber sampler (10 random sampling units, 1m²) were carried out from September 1999 to September 2000 and quarterly from December 2000 to September 2001 in the Bocaina and Água Comprida Streams. The EPT fauna in the Bocaina Stream was more diversified and more abundant than in the Água Comprida Stream. The EPT fauna was quite different in the two streams both in composition as in functional aspects. The results of this study indicate that there was not a clear seasonal pattern in the temporal variation of density.
Comunidades de Ephemeroptera, Plecoptera e Trichoptera em dois ribeirões de Mata Atlântica do sudeste do Brasil
Keywords: Ambientes lóticos; diversidade; EPT; insetos aquáticos; Aquatic insects; diversity; EPT; lotic environments